Approaches to assessing the demand for medical personnel in the Russian Federation - S. N. Tishkina; T. G. Alkhasov; D. V. Lukyantseva; T. P. Bezdenezhnykh (IRBIS LLC, 2019)
The availability of the adequate number of qualified health workforce is an important component of the National Health Program that guarantees affordable and high-quality medical care to the citizens of the Russian Federation. Health workforce planning can be efficient when all its elements are efficient; especially, the methods of assessing the demand for medical personnel and the arrangements for attracting skilled human resources (training programs for specialists, improved work contracts, incentives, and wage regulation).Aim: to review and analyze the current practice of assessing the demand for medical personnel and the reevant regulations in the Russian Federation.Materials and Methods. Regulatory documents and other publically available materials regarding the assessment of demand for medical personnel in the Russian Federation were analyzed; our special interest was focused on documents regulating the number of medical doctors. The review included the orders of the Ministry of Health of Russia, which established the methodology for calculating the demand for medical personnel, organizational standards of medical care, and procedures for the provision of medical care.Results. Two major approaches to the assessment of demand for medical personnel are used in Russia. According to the first approach, the deficit or surplus of the medical personnel is determined by comparing the actual number of employees with the staffing norms. The second approach suggests comparing the actual number of employees with the number calculated in accordance with the recommended methodology. Both approaches have disadvantages that reduce the likelihood of their practical efficiency.Conclusion. In Russia, the existing approaches to the assessment of the health workforce demand do not allow for long-term strategic planning and should be revised and optimized.